Soil fertility status of cassava fields treated by integrated application of manure and NPK fertilizer in Zambia - Biratu, G.K.; Elias, E.; Ntawuruhunga, Pheneas (Springer, 2019)
Cassava is a heavy feeder crop that can cause serious depletion to soil nutrient stocks. This research aimed to explore soil fertility status and nutrient supply capacity at different growth stages of cassava fields under combined application of organic manure and NPK fertilizers in two agroecologies of Zambia. Topsoil (0–20 cm) samples were collected from cassava fields treated with factorial combination of four levels of chicken manure (0, 1.4, 2.8, and 4.2 ton ha−1) and four levels of NPK (control, 50N-11P-41.5K, 100N-22P-83K, and 150N-33P-124.5P). The soils were sampled under the cassava canopy to determine soil pH, available phosphorus (AP), total nitrogen (TN), organic carbon (OC), cation exchange capacity (CEC), exchangeable bases and micronutrients (Fe, Cu, Mn, and Zn). The samples were collected before planting andafter establishment at 4, 8, and 12 months after planting (MAP).